MENYIKAPI KEBERADAAN BISNIS BENSIN ECERAN DI KELURAHAN KOTA BAMBU UTARA PALMERAH JAKARTA BARAT MENURUT UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Andi Setiawan (JURNAL LENTERA BISNIS, 2022)
Economic pressure for the survival of the family is the reason why some residents of Kota Bambu Utara Village, Palmerah, West Jakarta work as retail gasoline sellers. This activity is legally prohibited by law. The danger of fire threatens the safety of citizens at all times. The reason for the ignorance of the prohibition is not to justify the existence of this sale and purchase. Product that is easy to sell, the attitude of indifference or omission from officials and local residents, the absence of socialization of regulations and firm actions from local officials have made the number of retailers continue to grow. The result of the study found that the absence of standard operating procedures, the eaccuracy of the dosage and the purity of retail gasoline products do not meet the provisions of applicable laws. This study used descriptive qualitative method. The purpose of this paper is to determine the attitude of residents and local officials to the phenomenon of the widespread existence of retail gasoline kiosks according to the Consumer Protection Act.Keywords: Retail Gasoline, Consumer Protection Act.